Rosuvastatin can block pro-inflammatory actions of transgenic human C-reactive protein without reducing its circulating levels - Šilhavý, Jan; Zídek, Václav; Landa, Vladimír; Šimáková, Miroslava; Mlejnek, Petr; Škop, Vojtěch; Oliyarnyk, Olena; Kazdová, Ludmila; Mancini, Massimiliano; Saar, Kathrin; Schulz, Herbert; Hübner, Norbert; et al. (Cardiovascular therapeutics, 2014)
AIMS: Statins have antiinflammatory effects and are known to decrease risk of cardiovascular events and to reduce serum levels of C-reactive protein (CRP), a widely studied biomarker and potential mediator of inflammation and heart disease. However, it is unclear whether statins can block pro-inflammatory effects of human CRP independent of their ability to reduce serum levels of human CRP. Here, we investigated whether rosuvastatin could block pro-inflammatory effects of human CRP without reducing circulating levels of human CRP. METHODS AND RESULTS: We studied the antiinflammatory effects of rosuvastatin in spontaneously hypertensive rats (SHR) transgenically expressing human CRP (CRP-transgenic SHR) and in nontransgenic SHR lacking human CRP (nontransgenic SHR). The CRP-transgenic SHR is characterized by increased serum levels of human CRP and inflammation. In the CRP-transgenic strain, we found that rosuvastatin treatment decreased circulating levels of inflammatory response markers IL6 and TNFα without decreasing circulating levels of human CRP. In contrast, in the nontransgenic strain lacking human CRP, rosuvastatin treatment had little or no effect on IL6 and TNFα levels. Rosuvastatin also reduced cardiac inflammation and oxidative tissue damage, reduced epididymal fat mass, and improved adipose tissue lipolysis much more in the CRP-transgenic strain than in the nontransgenic strain. CONCLUSION: Rosuvastatin can protect against pro-inflammatory effects of human CRP in a manner that is not dependent on achieving a reduction in circulating levels of human CRP.
Keywords: fluorbenzeny; potkani inbrední SHR; Disease Models, Animal; antiflogistika; modely nemocí na zvířatech; Myocytes, Cardiac; Gene Expression Regulation; potkani transgenní; interleukin-6; kardiomyocyty; sulfonamidy; TNF-alfa; Inflammation Mediators; Male; Rats; lidé; Pyrimidines; Rosuvastatin Calcium; Humans; játra; Anti-Inflammatory Agents; mediátory zánětu; C-Reactive Protein; Tumor Necrosis Factor-alpha; rosuvastatin; Animals; zánět; Liver; spontaneously hypertensive rat; Rats, Inbred SHR; zvířata; transgenic; Rats, Transgenic; mužské pohlaví; rosuvastatin kalcium; regulace genové exprese; C-reaktivní protein; Interleukin-6; Fluorobenzenes; krysa rodu Rattus; Sulfonamides; Oxidative Stress; pyrimidiny; oxidační stres; C-reactive protein; Inflammation; cardiac inflammation